(x-6)(x-6)(3)=432

Simple and best practice solution for (x-6)(x-6)(3)=432 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)(x-6)(3)=432 equation:


Simplifying
(x + -6)(x + -6)(3) = 432

Reorder the terms:
(-6 + x)(x + -6)(3) = 432

Reorder the terms:
(-6 + x)(-6 + x)(3) = 432

Reorder the terms for easier multiplication:
3(-6 + x)(-6 + x) = 432

Multiply (-6 + x) * (-6 + x)
3(-6(-6 + x) + x(-6 + x)) = 432
3((-6 * -6 + x * -6) + x(-6 + x)) = 432
3((36 + -6x) + x(-6 + x)) = 432
3(36 + -6x + (-6 * x + x * x)) = 432
3(36 + -6x + (-6x + x2)) = 432

Combine like terms: -6x + -6x = -12x
3(36 + -12x + x2) = 432
(36 * 3 + -12x * 3 + x2 * 3) = 432
(108 + -36x + 3x2) = 432

Solving
108 + -36x + 3x2 = 432

Solving for variable 'x'.

Reorder the terms:
108 + -432 + -36x + 3x2 = 432 + -432

Combine like terms: 108 + -432 = -324
-324 + -36x + 3x2 = 432 + -432

Combine like terms: 432 + -432 = 0
-324 + -36x + 3x2 = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(-108 + -12x + x2) = 0

Factor a trinomial.
3((-6 + -1x)(18 + -1x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6

Subproblem 2

Set the factor '(18 + -1x)' equal to zero and attempt to solve: Simplifying 18 + -1x = 0 Solving 18 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -1x = 0 + -18 -1x = 0 + -18 Combine like terms: 0 + -18 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18

Solution

x = {-6, 18}

See similar equations:

| 3(2x-4)=2(3x+7) | | 14+3v=v+6 | | 3(x+2)+9=6x-3(-5+x) | | 6y+50=8y+14 | | -5x+14=-14-4x | | 2(x+4)=11(x+5) | | 5x+7+3=10 | | -2.5x+2=0.5(8-6) | | 4x+9x-2x=19+3 | | 6x+4x-6-2x-x-12=10 | | 30x+20=18 | | 2(6x+2)=3(3x-3) | | 111111111*111111111=x | | 6+1x=4 | | 6X-3=8+6x | | F(x)=2x^2+13x+6 | | 2x+62=12x-58 | | d=25x+16 | | 100+30x=100+30x | | 2a+5+2a=6a+5-2a | | 2(9x-4)=11 | | x^2+14.6x-2093=0 | | 5(2x-4)=4+3x | | 4.50+14.40=4.50(p+3) | | 5x+3(2x-5)=-6x-15+17x | | 7c-(3c+8)=0 | | X^2+225x-8=0 | | 7x-151=-12x+96 | | 15=30t+(0.5x-9.8)t^2 | | 3x^2-45x+164=-4 | | 7v=2v-10 | | 5x+4=4+8x |

Equations solver categories